2006
DOI: 10.1111/j.1468-2958.2006.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Analysis of Imagined Interactions

Abstract: This study examines imagined interactions (IIs) among young adults in the United States, Thailand, and Japan. A comparison of means across cultures on II characteristics reveals that the Japanese participants have the widest variety of II partners, whereas the American participants are the most self‐dominant in their IIs and demonstrate the most II frequency. As for II functions, Japanese and Thai participants keep conflict alive via their IIs more than the Americans, whereas the Thais utilize the II rehearsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…that are so often described in the Thai research literature as related to hierarchical or status differentials are, in fact, frequently utilized regardless of the age or rank of the interactant. For example, kreng jai (difference, deference and consideration merged with respect) can be called upon when interacting not only to those of superior status (e.g., due to age, rank), but also to those of equal or inferiors status as well (see McCann, 1992; McCann & Honeycutt, 2006, for an in‐depth discussion of kreng jai ). According to Komin (1990), a Thai can feel kreng jai toward one's equal, one's inferior, or even one's subordinate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…that are so often described in the Thai research literature as related to hierarchical or status differentials are, in fact, frequently utilized regardless of the age or rank of the interactant. For example, kreng jai (difference, deference and consideration merged with respect) can be called upon when interacting not only to those of superior status (e.g., due to age, rank), but also to those of equal or inferiors status as well (see McCann, 1992; McCann & Honeycutt, 2006, for an in‐depth discussion of kreng jai ). According to Komin (1990), a Thai can feel kreng jai toward one's equal, one's inferior, or even one's subordinate.…”
Section: Discussionmentioning
confidence: 99%
“…Connections with others are stressed, fitting in is valued, and “self‐dominance” and “boldness” (at least in spoken interactions) are largely discouraged. As Thais move through their youth, they are taught to kreng jai (show difference, deference), be accommodative of others, and display choei (stay silent, keep feelings to oneself) in potentially uncomfortable situations (McCann, 1992; McCann & Honeycutt, 2006; Mulder, 1996). It is argued herein that these dissimilar traditions influence intra‐ and intergenerational communicative behaviors in differing and unique ways, making research such as this a valuable portico into how modes of thought and communication vary across cultures.…”
mentioning
confidence: 99%
“…1 A third limitation is that causality cannot be inferred from the data; although we predicted that IIs predict dissent, it is possible that dissent episodes trigger IIs too. Future researchers may consider the role that culture plays in IIs and the dissent process considering that Americans are the most self-dominant in IIs (McCann & Honeycutt, 2006). Moreover, future research might consider how IIs function in the small group context with class assignments because individuals have third-party imagined interactions about others, not just themselves (Porter, 2010(Porter, -2011.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Berkos (2012Berkos ( -2013 discovered that students who use IIs before e-mailing an instructor are more likely to use prosocial compliance-gaining strategies and less likely to make verbal demands in an e-mail. Because instructional dissent is considered a response to potential instructor-student conflict , and because IIs are most commonly used to process and rehearse perceived conflict (Allen & Berkos, 2005-2006Honeycutt, 2003Honeycutt, -2004Zagacki et al, 1992), it is our contention that IIs are used by students who have a desire to communicate instructional dissent.…”
Section: Imagined Interactionsmentioning
confidence: 98%
“…This finding emphasizes the inclusion of others regarding self-constructed beliefs about oneself and suggests that East Asians are more likely to evaluate the presence and opinion of others as more critical when it comes to self-image. In addition, a cross-cultural analysis (McCann and Honeycutt, 2006) comparing imagined interaction, a cognitively represented conversation experienced as internal dialogues, among participants from the United States, Thailand and Japan found that American participants were the most self-dominant in their imagined interaction while the Japanese participants had the widest range of imagined interaction partners. This result shows that, compared with Westerners, people in non-Western cultures were more sensitive towards others than to the self, even in imagined interactions.…”
Section: Discussionmentioning
confidence: 99%